2019
DOI: 10.1186/s12864-019-5929-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening of genes encoding adhesion factors and biofilm production in methicillin resistant strains of Staphylococcus aureus isolated from Palestinian patients

Abstract: Background Intercellular adhesion and biofilm production by Staphylococcus aureus makes these bacteria resistant to antimicrobial therapy. Here, Methicillin-resistant Staphylococcus aureus (MRSA) strains were characterized and the prevalence of genes encoding adhesion factors and biofilm formation was determined. Results All 248 MRSA isolates identified by cefoxitin disc diffusion were positive for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 57 publications
6
25
4
3
Order By: Relevance
“…The biofilm-producing S. aureus strains isolated from food in this study carried agrI, II, or III, while other studies found that the majority (60%) of biofilm-producing S. aureus were the carriers of agrIII [6]. In S. aureus isolated from humans in this study, the agrI was more predominant in biofilm producers followed by agrII, which disagreed with a previous study in Palestine that reported biofilm-producing S. aureus isolated from humans mainly possessed agrI and agrIII [50]. It was reported that agr expression can restrict biofilm formation allowing the colonization of a new surface by dispersion of the bacterium from a previously formed biofilm [12,61].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The biofilm-producing S. aureus strains isolated from food in this study carried agrI, II, or III, while other studies found that the majority (60%) of biofilm-producing S. aureus were the carriers of agrIII [6]. In S. aureus isolated from humans in this study, the agrI was more predominant in biofilm producers followed by agrII, which disagreed with a previous study in Palestine that reported biofilm-producing S. aureus isolated from humans mainly possessed agrI and agrIII [50]. It was reported that agr expression can restrict biofilm formation allowing the colonization of a new surface by dispersion of the bacterium from a previously formed biofilm [12,61].…”
Section: Discussioncontrasting
confidence: 99%
“…Here, the fnbB gene was rarely detected among non-biofilm-producing isolates but found in all biofilm-producing isolates from food matrices and humans. These findings were in discordance with a previous reports where either the fnbB gene was not detected in biofilm-producing isolates [6] or detected in a low level (29.0%) in MRSA isolated from humans [50]. However, a previous study reported that fnbB occurred frequently (99.5%) in S. aureus isolated from humans [46].…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Some S. aureus is ica‐independent, in which the biofilm‐associated protein (Bap) is important for bacterial accumulation (Yadav et al., 2015). In addition, the biofilm of Staphylococcus is under the control of several genetic loci, namely, sarA (staphylococcal accessory regulator), luxS , and agr QS systems (Azmi, Qrei, & Abdeen, 2019). Several spice essential oils and their components have been revealed to show inhibitory effects on the production of EPS or the in‐depth regulatory genes.…”
Section: Bacterial Biofilmmentioning
confidence: 99%